3D-FSE-XETA-T1WI平扫序列在评估MCA狭窄中的诊断价值：VWI多序列与DSA的对照研究(The Diagnostic Value of 3D-FSE-XETA-T1WI Plain Scan Sequence in Evaluating MCA Stenosis: A Control Study of VWI Multi-Sequence and DSA) - 尹雪梅，赵晓慧，李文菲，吴磊，刘兰祥，张俊(YIN Xuemei, ZHAO Xiaohui, LI Wenfei, WU Lei, LIU Lanxiang, ZHANG Jun) (Zhongguo cuzhong zazhi, 2025)
目的 探讨磁共振血管壁成像（vessel wall imaging，VWI）多序列与DSA评估大脑中动脉（middle cerebral artery，MCA）狭窄率的差异，明确最优序列的诊断价值。 方法 回顾性收集2022年3月1日—2023年8月31日在秦皇岛市第一医院接受VWI及DSA检查且证实MCA-M1段狭窄或闭塞的患者影像及临床资料。利用组内相关系数（intra-class correlation coefficient，ICC）评估VWI 5种序列[三维快速自旋回波序列扩展回波链采集技术（3D fast spin echo with an extended echo train acquisition，3D-FSE-XETA）-T1WI平扫和增强、2D-T2WI、2D-T1WI平扫和增强]与DSA测量MCA-M1段管腔狭窄率之间的一致性，通过绘制ROC曲线比较5种序列诊断重度狭窄及闭塞的效能。 结果 共纳入70例患者，平均年龄为（58.16±10.68）岁，男性43例（61.4%）。VWI 5种序列与DSA测量MCA-M1段狭窄率总的一致性较高[ICC 0.96（0.94～0.97），P<0.001]；其中3D-FSE-XETA-T1WI平扫序列的一致性最好[ICC 0.88（0.81～0.93），P<0.001]，诊断重度狭窄及闭塞的效能优于2D序列[AUC 0.78（0.67～0.87），P<0.05]，与3D增强序列相当（P=0.143）。 结论 VWI 3D-FSE-XETA-T1WI平扫序列在评估MCA-M1段狭窄率方面优于其他序列，可作为临床术前辅助DSA评估狭窄程度的一种有效方法。Abstract: Objective To explore the differences in evaluating the stenosis rate of the middle cerebral artery (MCA) by comparing multi-sequence of magnetic resonance vessel wall imaging (VWI) with DSA, and to clarify the diagnostic value of the optimal sequence. Methods A retrospective collection of imaging and clinical data was conducted on patients who visited the First Hospital of Qinhuangdao from March 1, 2022, to August 31, 2023, who were confirmed to have stenosis or occlusion of the MCA-M1 segment by VWI and DSA examinations. The intra-class correlation coefficient (ICC) was used to evaluate the consistency in measuring the luminal stenosis rates of the MCA-M1 segment between five VWl sequences [3D fast spin echo with an extended echo train acquisition (3D-FSE-XETA)-T1WI plain scan+enhancemend, 2D-T2WI, 2D-T1WI plain scan+enhancemend] and DSA. ROC curves were plotted to compare the diagnostic efficacy of the five sequences for severe stenosis and occlusion. Results A total of 70 patients were included, with an average age of (58.16±10.68) years, among whom 43 were male (61.4%). The overall consistency of the MCA-M1 segment stenosis rates measured by the five sequences of VWI and DSA was excellent [ICC 0.96 (0.94-0.97), P<0.001]. Among these sequences, the 3D-FSE-XETA-T1WI plain scan sequence had the best consistency [ICC 0.88 (0.81-0.93), P<0.001], and its diagnostic efficacy for severe stenosis and occlusion was superior to that of the 2D sequences [AUC 0.78 (0.67-0.87), P<0.005] and comparable to that of the 3D enhanced sequences (P=0.143). Conclusions The 3D-FSE-XETA-T1WI plain scan sequence in VWI is superior to other sequences in evaluating the stenosis rate of the MCA-M1 segment and can serve as an effective method to assist DSA in evaluating the stenosis severity before clinical surgery.